On the determination of the actual solar energy resources - Филенко, В. В. (Інститут енергетичних машин і систем ім. А. М. Підгорного Національної академії наук України, 2015)
PV-farm simulation results in software package RETScreen and PVSYST for conditions of the plain part of Ukraine are posted. The simulation results with the estimated model and the results of the operation of a real station were compared. The estimated model is built based on the direct and diffuse solar radiation. Imposed approaches to determining the potential of solar energy and photovoltaic panels classification based on the identification of three generations of photovoltaic cells. The technological scheme of laboratory research stand fixing the parameters of the photoelectric: current voltage and power electric current running time of the day and the total energy production was described. Provided recommendations for areas application software systems. RETScreen 4.0 can be successfully used in the early stages of decision-making, but gives high accuracy of seasonal changes in solar insolation.